(untitled) (Journal of the College of Education for Women, 2019)
Research problem:Problem of current research can determine the dimensions to answer the following question: The effect of teaching using the six thinking hats on academic achievement for students in the second grade average in the subject of Family Education. The importance of research: research is gaining importance in terms of:1. That this research is the first of its kind in the researcher’s knowledge _ which deals with the teaching of Family Education by using the six hats, the researcher hopes to fill a gap in the educational field and serve in other studies serve the materials home economics. 2. Keep pace with the new field of modern education and strategies. 3. Highlight on the educational strategy in the field of creative teaching of family educationwhich is the material from which urgently need to renew teaching methods for student.. 4. Get out of the monotony of the traditional method of teaching in a way and a new strategy develops the teacher and learners different thinking skills through educational situations faced and how its accustomed to reflect on attitudes and problems and get rid of the negative aspects of directed thinking.5. The result of this study can contribute to the benefit of employees over the formation of a substance in the formulation of how content material in accordance with the strategies of modern learning and that develop multiple aspects of multi learner.Aim of the research:The current research aims to find out The effect of teaching using the six thinking hats on academic achievement for students in the second grade average in the subject of family educationHypothesis of Search:No statistically significant differences at the level of (0.05) between the average degrees Students who studied using the six hats and the average score for students who studied in the traditional way in the test grades dimensional.Search Results:Found significant differences at the level of (0.05) between the average grades of female students who studied the use of strategy six hats and between the average grades of female students who studied in the traditional manner in the test grades dimensional